Melintasi Dimensi Spiritual: Tradisi Wiwitan dalam Spiritualitas Manusia menurut Mircea Eliade - Sudarman, Mei Ariani; Maharani, Septiana Dwiputri (HUMANIKA, 2024)
Humans live in interaction with culture and tradition, both those inherited from ancestors and those that have undergone acculturation. There is a spiritual touch between tradition and humans, which is the meaning given to the series of rituals that eventually evolve into a tradition. The relationship between humans and their God is then represented in a tradition, one of which is Wiwitan. This tradition, which has existed since ancient times, is a routine practice for farmers before starting their harvest, with the hope that their harvest will be abundant. This study is philosophical research that uses the method of philosophical reflection. This philosophical reflection involves an examination of key concepts in the thinking of Eliade, such as homo religiosus, hierophany, and the sacred and the profane. The researcher can explore how Eliade's ideas can be applied to understand the Wiwitan tradition. A review of the historical literature on Wiwitan, case studies, or anthropological literature also helps to understand the context of the evolution and relevance of the Wiwitan tradition through the ages. The results of this study show that the Wiwitan tradition is an important part of the Javanese farmer's life, which not only functions as a ceremonial rite before the harvest but also reflects their view of nature as a sacred space. In this ritual, farmers honor nature and Dewi Sri, the goddess of fertility, asking for blessings and protection. With the concept of homo religiosus as proposed by Mircea Eliade, Wiwitan reflects the basic human need to connect with the sacred, providing spiritual meaning amidst changing times.